[Architecture majors "Working the Night Away"] - Cas' Szukalski::::::photographer::: (1950)
On back: 'Architects work overtime. Students in the Architectural Engineering Department put in many overtime hours each week in the spacious and modernistic drafting lab. Shown here is a group of junior and senior architectural majors "Working the Night Away" on their design problems.', George Hasslein, founding dean of the College of Architecture and Environmental Design, standing in back.